Clinical variability of osteogenesis imperfecta linked to COL1A2 and associated with a structural defect in the type I collagen molecule. Issue 6 (June 1989) - Superti-Furga, A; Pistone, F; Romano, C; Steinmann, B
Abstract : We report a family in which dominant osteogenesis imperfecta segregates with a COL1A2 haplotype and is associated with a structural defect in the helical region of the type I procollagen molecule. All affected subjects had short stature, dentinogenesis imperfecta, and myopia; however, great differences were observed in the number of fractures and in the degree of bone deformity. Identical biochemical changes were found in the type I collagen molecules synthesised by fibroblasts of subjects with severe or minimal bone fragility. These results confirm that mutations in the triple helical region of alpha 2(I) chains produce a milder phenotype than analogous mutations in the alpha 1(I) chains, but indicate that, in addition to defects in the type I collagen molecule, other factors may modulate the degree of bone involvement in osteogenesis imperfecta.